2022
DOI: 10.3389/fcvm.2022.1003104
|View full text |Cite
|
Sign up to set email alerts
|

Midkine—A novel player in cardiovascular diseases

Abstract: Midkine (MK) is a 13-kDa heparin-binding cytokine and growth factor with anti-apoptotic, pro-angiogenic, pro-inflammatory and anti-infective functions, that enable it to partake in a series of physiological and pathophysiological processes. In the past, research revolving around MK has concentrated on its roles in reproduction and development, tissue protection and repair as well as inflammatory and malignant processes. In the recent few years, MK's implication in a wide scope of cardiovascular diseases has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 152 publications
1
2
0
Order By: Relevance
“…and from complications for hypothyroidism-related cardiovascular disease, MK has been associated with a number of cardiovascular diseases, and many research investigations on cardiovascular diseases have found elevated MK expression. (Majaj and Weckbach 2022).Estimating serum electrolyte levels may be essential to controlling hypothyroid patients; it should be taken into account as it can assist in preventing future issues (Koner and Chaudhuri 2022). Statistical analysis did not show a significant difference in sodium levels among the groups, This result matched past studies (Wiwanitkit 2020).…”
Section: Discussionsupporting
confidence: 54%
“…and from complications for hypothyroidism-related cardiovascular disease, MK has been associated with a number of cardiovascular diseases, and many research investigations on cardiovascular diseases have found elevated MK expression. (Majaj and Weckbach 2022).Estimating serum electrolyte levels may be essential to controlling hypothyroid patients; it should be taken into account as it can assist in preventing future issues (Koner and Chaudhuri 2022). Statistical analysis did not show a significant difference in sodium levels among the groups, This result matched past studies (Wiwanitkit 2020).…”
Section: Discussionsupporting
confidence: 54%
“…It is composed of two domains, each including three antiparallel β-strands and various heparin-binding consensus sites [14], which enable its binding to heparan sulfate and chondroitin sulfate and the formation of a molecular complex with proteoglycans [18]. Importantly, MDK binding to sulfated glycosaminoglycans (GAGs) leads to interactions with several key receptors, including protein-tyrosine phosphatase-ζ (PTP-ζ), syndecans, low-density lipoprotein receptor-related protein (LRP), α4β1 and α6β1 integrins, and neurogenic locus notch homolog protein 2 (Notch-2), while it has also been reported to phosphorylate the cell-matrix adhesion proteins paxillin and focal adhesion kinase (FAK) [19] (Figure 1). Such interactions prompt, in turn, the activation of major pro-survival signaling pathways, including Src family kinase, phosphoinositide 3 kinase (PI3K), mitogen-activated protein kinase (MAPK), and nuclear factor kappa B (NF-κΒ), which in turn promote various cellular functions, such as cell proliferation, survival, adhesion, migration, and angiogenesis (Figure 2) [20,21].…”
Section: Mdk-mediated Signaling and Cellular Functionmentioning
confidence: 99%
“…MDK was shown to be associated with cardiac pathology and angiogenesis 44 . It has been demonstrated that MDK is both necessary and sufficient to promote endothelial growth factor A cell proliferation in growing collaterals 45 .…”
Section: Expression Of Vascularization-related Genesmentioning
confidence: 99%